Fully endoscopic clipping of anterior circulation cerebral aneurysms through transpalpebral approach: One step closer to robotic neurovascular surgery?. (June 2021) - Ferrarez, C.E.; Bertani, R.; Koester, S.; Perret, C.; Leal, R.S.; Gusmão, S.; Maluf, F.B.; Oliveira, M.M.; Landeiro, J.A.
Highlights: Fully endoscopic clipping of internal carotid and middle cerebral artery aneurysms may be safe and feasible. Fully endoscopic approaches may allow neurosurgeons to take the most advantage of minimally invasive approaches, such as the transpalpebral approach. In fully endoscopic approaches, it may be feasible to attain both proximal and distal vascular control of intracranial aneurysms. Fully endoscopic approaches may pave the way for innovation in vascular neurosurgery.